PEMANFAATAN MEDIA FLASHCARD DIGITAL BERBASIS AUDIO UNTUK MENINGKATKAN MOTIVASI SISWA KELAS II SEKOLAH DASAR DI KABUPATEN AGAM - Hamda, Dzakya; Dwi Fortuna, Dinda; Safitri, Dinda; Fitria, Yanti; Kharisma, Inggria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The teaching of Indonesian at primary school level encompasses four key skills: listening, speaking, reading and writing. However, in practice, pupils in the lower years often struggle to understand the information conveyed by their teachers, which affects their motivation to learn. The aim of this study is to describe the use of digital flashcards with audio in the teaching of Indonesian. The method applied in this study is descriptive qualitative. This method was chosen because it facilitates direct observation of the learning process in the classroom and allows for the assessment of changes in students’ motivation and listening skills. The results of the study indicate that the majority of students appeared enthusiastic and more focused when participating in learning activities supported by digital audio-based flashcards.